Taguchi method for optimising the sintering parameter of the Metal Injection Moulding (MIM) compacts - Jamaludin, Khairur Rijal; Muhamad, N.; Ab. Rahman, M. N.; Amin, S. Y. M.; Ahmad, S.; Ibrahim, M. H. I (2009)
Sintering parameters of the SS316L water atomized injection moulded compact has been optimized for its best sintered density. The L9 (34) Taguchi orthogonal array is used in the experiment while sintering temperature, sintering time, heating rate and cooling rate was selected as factors that influenced the sintered density. The sintering environment was in the vacuum and four replications were done for each trial. The analysis of variance shows that the confident level for the experiment was 99.5 % (Î± = 0.005) and all factors are highly significant at Î± = 0.005 to the sintered density. The study concluded that the heating rate has the highest influence to the sintered density (41.29 %) followed by sintering temperature (31.60 %), sintering time (11.13 %) and cooling rate (11.10%). The optimum sintered density obtained is 98.48 % of the theoretical density and the optimum parameter has been verified that the sintered density obtained is in a range of confident interval